Development of sustainable polymer-based dielectric composites from agricultural waste: A review - Mekha, K. B.; Nurhafizah, Abu Talip Yusof; Sudhakar, Kumarasamy; Norazwina, Zainol; Nurulfadzilah, Hasan; Mohamad Shaiful, Abdul Karim (Elsevier Ltd, 2024)
Dielectrics are essential for storing and controlling electrical energy in the electrical and electronic industries. However, their production from non-renewable sources raises environmental concerns. This review investigates sustainable polymer-based dielectric composites made from agricultural waste, focusing on the various parameters that affect dielectric characteristics. These composites offer improved dielectric properties and contribute to waste reduction and environmental sustainability. Agricultural waste, including crop residues and by-products, offers a promising, sustainable source of dielectric composite materials. This review also highlights the feasibility of using agricultural waste-based polymer dielectric composites for dielectric material in various electronics applications. Dielectric composite's permittivity is influenced by carbon, oxygen, filler, temperature, cellulose, and morphological changes. Biodegradable materials like agricultural waste, which have good fibre and carbon content, can produce good dielectric constants, making them suitable for antennas and microwave absorbers. In conclusion, the review underscores the importance of sustainable practices in dielectric composite material development and the valuable role of agricultural waste in advancing environmentally friendly solutions.